2009
DOI: 10.1111/j.1442-2050.2009.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's esophagus and endoscopically assessed esophagogastric junction integrity in 1000 consecutive Turkish patients undergoing endoscopy: a prospective study

Abstract: Barrett's esophagus (BE) appears to be more common in Western than in Asian countries. BE is a complication of gastroesophageal reflux disease (GERD). Anatomical abnormalities of the esophagogastric junction (EGJ) are an important factor in the pathogenesis of GERD. We aimed to determine the prevalence of BE in Turkey, which is geographically located between Europe and Asia, and to investigate the frequency of BE according to the degree of anatomical disruption in the EGJ. This prospective study was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They were published between 1985 and 2022. Sixteen studies were performed in Asia, 19 34 16 in Europe, 35 50 14 in America, 51 64 and 1 in Oceania. 65 …”
Section: Resultsmentioning
confidence: 99%
“…They were published between 1985 and 2022. Sixteen studies were performed in Asia, 19 34 16 in Europe, 35 50 14 in America, 51 64 and 1 in Oceania. 65 …”
Section: Resultsmentioning
confidence: 99%
“…19,20 The prevalence rates reported form Turkey are markedly lower than those determined in western countries. In their prospective study, Odemiş et al 21 have reported a BE prevalence of 1.2% in Turkish patients undergoing endoscopy for any reason. In a retrospective Turkish study on 18,766 patients undergoing endoscopy for various reasons, the prevalence of BE has been reported as 0.4%.…”
Section: Discussionmentioning
confidence: 96%